(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Feasibility studies about processing lignocellulosic reinforced polymer composites by injection moulding have been receiving widespread attention nowadays. The aim of this research was to identify the optimal selection of parameters, significant parameters, and effects of the injection-moulding parameters during the post filling-stage. In this simulation study, the modelling of an automotive component, namely the Proton Waja CAMPRO car engine cover, required a 3-D model and mesh generation to obtain the mouldability of its composite material using the injection moulding process. Autodesk Moldflow InsightÂ® was used to simulate and analyse the injection-moulding process. Therefore, 60 wt% of wood filler reinforced polypropylene was evaluated under optimised injection parameters (injection temperature, mould temperature, injection pressure and flow rate) during the post-filling stage simulation (filling time, average velocity, volumetric shrinkage, sink marks, and shear stress). In addition, numerical simulation by the Taguchi method consisting of S/N ratio and ANOVA were used in this research to determine which significant factors would affect all responses. Based on the numerical simulation results, the flow rate shows the most significant parameter for the reduction of filling time, volumetric shrinkage, sink marks, and shear stress while also enhancing the average velocity on the car engine cover.Â